RNF126, 168 and CUL1: The Potential Utilization of Multi-Functional E3 Ubiquitin Ligases in Genome Maintenance for Cancer Therapy - Hae Ryung Chang (Biomedicines, 2023)
Ubiquitination is a post-translational modification (PTM) that is involved in proteolysis, protein–protein interaction, and signal transduction. Accumulation of mutations and genomic instability are characteristic of cancer cells, and dysfunction of the ubiquitin pathway can contribute to abnormal cell physiology. Because mutations can be critical for cells, DNA damage repair, cell cycle regulation, and apoptosis are pathways that are in close communication to maintain genomic integrity. Uncontrolled cell proliferation due to abnormal processes is a hallmark of cancer, and mutations, changes in expression levels, and other alterations of ubiquitination factors are often involved. Here, three E3 ubiquitin ligases will be reviewed in detail. RNF126, RNF168 and CUL1 are involved in DNA damage response (DDR), DNA double-strand break (DSB) repair, cell cycle regulation, and ultimately, cancer cell proliferation control. Their involvement in multiple cellular pathways makes them an attractive candidate for cancer-targeting therapy. Functional studies of these E3 ligases have increased over the years, and their significance in cancer is well reported. There are continuous efforts to develop drugs targeting the ubiquitin pathway for anticancer therapy, which opens up the possibility for these E3 ligases to be evaluated for their potential as a target protein for anticancer therapy.